Amphotericin B colloidal dispersion: an effective drug for the treatment of mucormycosis in China - Liu, Juntao; Ma, Xiaoxu (Frontiers in Cellular and Infection Microbiology, 2023)
Objective Mucormycosis has emerged as an increasingly important cause of morbidity and mortality in immunocompromised patients, but the effective drugs for the treatment are limited. Hence, the study aimed to summarize the characteristics of mucormycosis in patients with hematological malignancies, and investigate the efficacy and safety of Amphotericin B Colloidal Dispersion (ABCD) in treating mucormycosis. Methods In this study, patients with mucormycosis complicated by hematological malignancies who received ABCD at the First Affiliated Hospital of Zhengzhou University from April 2021 to May 2022 were retrospectively enrolled. The clinical data of the enrolled patients were collected, and then, the drug response at 2 weeks, 4 weeks, and the end of treatment; the survival rate at 4, 8, and 12 weeks; and the laboratory-related indicators and adverse events (AEs) associated with ABCD were evaluated. Results In total, 9 patients with mucormycosis complicated by hematological malignancies were enrolled. The main symptoms were fever, cough, and chest pain. In addition, reversed halo signs (RHS) were found on chest CTs. The responses to ABCD at 2 weeks, 4 weeks, and the end of treatment were 100% (9/9), 77.8% (7/9), and 77.8% (7/9), respectively. The survival rates of the patients at 4, 8, and 12 weeks were 77.8% (7/9), 66.7% (6/9), and 66.7% (6/9), respectively. Among laboratory-related indicators, white blood cell (WBC) counts were significantly increased from baseline after 1 and 2 weeks of ABCD treatment (P<0.05), whereas neutrophil counts were only increased significantly from baseline at 2 weeks post-treatment (P<0.05). The most common AEs were infusion-related AEs manifesting as fever, chills, and pruritus. Moreover, none of the patients suffered from renal injury once again. Conclusion ABCD is a promising treatment strategy for patients with mucormycosis complicated by hematologic malignancies, showing remarkable efficacy and safety.